Garner's administrative law - Jones, Brian (Brian L.); Thompson, Katharine, LLB.; Garner, J. F. (John Francis), 1914- (London : Butterworths, 1985)
Includes index
Rev. ed. of: Administrative law / by J.F. Garner. 5th ed. 1979.
Includes bibliographical references (p. [547]-553) and index.
Keywords: Administrative law -- Great Britain